Miller Fisher syndrome developed after a previous COVID-19 infection (case report) - V. A. Malko; P. V. Klimov; M. P. Topuzova; I. V. Yarush; K. V. Simakov; T. M. Alekseeva (Нервно-мышечные болезни, 2021)
Miller Fisher syndrome is one of the forms of Guillain–Barrе́ syndrome, characterized by a clinical triad that includes ophthalmoplegia, ataxia and areflexia, with the possible addition of moderate peripheral tetraparesis. During the year that has passed since the start of the pandemic of the new coronavirus infection COVID‑19, international publications have presented a few cases of Miller Fisher syndrome, which developed in patients at different times after the COVID‑19 infection – from 3–5 days to 3 weeks. The article presents a description of a clinical case of Miller Fisher syndrome, which occurred with 34‑year‑old man 21 days after the COVID‑19 infection. The clinical manifestations of Miller Fisher syndrome were typical and included diplopia, areflexia, and ataxia. At the beginning of the disease, there was a transient episode of speech impairment in the form of mild dysarthria. Oculomotor disorders predominated in the clinical picture over other components of the classical triad. On the background of treatment with human immunoglobulin G, there was a complete regression of symptoms.This description of Miller Fisher syndrome, which developed after the postponed infection with COVID‑19, is the first in Russia. The presented case demonstrates the ability of the SARS‑CoV‑2 virus to induce the development of an autoimmune disease. Practitioners should take into account the possibility of Miller Fisher syndrome developing in the event of an acute onset of diplopia, ataxia and areflexia in patients after a previous COVID‑19 infection.